A Refined Model of the CFTR Membrane Transporter as a Tool to Revert Misbehavior - Pedro M. S. Suzano; Michael González-Durruthy; Ricardo J. Ferreira; Cátia A. Bonito; Margarida D. Amaral; Daniel J. V. A. dos Santos (Chemistry Proceedings)
ABC proteins are large transmembrane efflux pumps that export substrates against the concentration gradient through ATP hydrolysis. Due to their efflux capabilities, they are crucial in drug metabolism. Point mutations in ABC proteins can lead to many forms of illness by causing protein misfolding and misbehavior. CFTR, or ABCC7, is a member of this transporter family, which, when mutated, can lead to cystic fibrosis, the most common life-shortening rare disease. Here, we report a refined and functional model of CFTR using in silico methods, aiming at further understanding anion permeation and the impact of different mutations on the gating mechanism to shine light on ways to reverse mutations’ effects.